2019
DOI: 10.1007/s12040-019-1166-x
|View full text |Cite
|
Sign up to set email alerts
|

Differences in natural gamma radiation characteristics of Erinpura and Malani granites in NW India

Abstract: In NW India, large volumes of exposed Neoproterozoic basement rocks are formed by two magmatic suites, Erinpura granites as a late thermal event with respect to the ∼1 Ga Delhi Orogeny and the younger Malani igneous suite (770-750 Ma). Average uranium and thorium equivalent concentrations (in ppm) inferred from spectroscopic gamma radiation survey are higher in Malani rocks (Th 47.33 ppm and U 6.95 ppm) as compared to the Erinpura granites (Th 33.55 ppm and U 4.77 ppm). These values are considerably above the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 56 publications
1
3
0
Order By: Relevance
“…For quality control of the gamma radiation (GR) data, comparison with geochemical data is necessary. Previously, we have substantiated the general significance of indirect GR measurements with the RS 230 equipment (Scharfenberg et al 2019). This study showed good correlation of U and Th concentrations derived from in situ measurements and data measured by ICP-MS.…”
Section: Measurements Of Natural Gamma Radiationsupporting
confidence: 73%
See 2 more Smart Citations
“…For quality control of the gamma radiation (GR) data, comparison with geochemical data is necessary. Previously, we have substantiated the general significance of indirect GR measurements with the RS 230 equipment (Scharfenberg et al 2019). This study showed good correlation of U and Th concentrations derived from in situ measurements and data measured by ICP-MS.…”
Section: Measurements Of Natural Gamma Radiationsupporting
confidence: 73%
“…A-type granites (Loiselle and Wones 1979;Eby 1992) are typical of intra-plate, often anorogenic settings. They are the most abundant in Proterozoic terranes, such as the Malani Igneous suite in NW India (Eby and Kochhar 1990;de Wall et al 2018), and are characterized by generally high radioelement concentrations (Scharfenberg et al 2015(Scharfenberg et al , 2019 resulting in higher RHP (Singh and Vallinayagam 2012). Therefore A-type granites commonly rank to high-heat-producing granites (HHP granites).…”
Section: Heat-producing Classification and Comparison With Other Granmentioning
confidence: 99%
See 1 more Smart Citation
“…Felsic rocks of the Malani Igneous Suite are well known for their high radiogenic heat production [84]. The Malani granites are characterized by high but varying Th and U concentration [85]. Some intrusions such as granites forming the Mt.…”
Section: A-type Malani Granitesmentioning
confidence: 99%